A Brief Overview of the South African Legal Framework for Marine Pollution with Reference to Land-Based Marine Pollution - Cliff Sibusiso Dlamini (Challenging Issues on Environment and Earth Science Vol. 1, 2021)
There exist arrays of legal instruments that provide guidance and legislative procedures for marine pollution processes and issues in the Republic of South Africa. The aim of this study is to briefly review and synthesize literature on the existing legislative framework. From the set of documents reviewed, it sometimes becomes unclear which one is applicable to what, under what circumstances and to what extent. Some light is shed here in this regard, indicating most especially the irreplaceable and authoritative instrument/s that supercedes others. Furthermore, the study briefly mentions the classification of laws and policies based on common law, doctrines of equity, and statutes of general application. The South African Legal System thrives upon four main sources that include (i) legislations, (ii) court decisions, (iii) common law, and (iv) customary law and indigenous law. Whilst case laws and indigenous laws have not been touched upon in any way, the reason for this is not farfetched as environmentalism is relatively a new area of societal activity. The issue of supremacy in conflict resolution and arbitration is raised, citing a noteworthy international case that becomes applicable to any signatory to the United Nations Convention of the law of the Seas. Light is shed upon the root base of marine pollution’s legal framework, citing key sections of the Constitution of the Republic, Environmental laws/statutes, policies and bye laws. The features enshrined in the United Nations Convention of the Law of the Seas is discussed in relation to to the national hierarchy of environmental laws , including bye laws.. An attempt is also made to enumerate four broad areas around which marine pollution cases could require adjudication. In addition, the study looks at issues of liability where it is assumed the State itself seems to be the e perpetrator (or not). This is exemplified with a case from the Pace International Law Review. Customary law and general International Principles of law are brought into examination using principles contained in the Corfu Channel Case of 1949 and subsequent Declarations. Taking a look at the South African general Legislative framework, the prominence of the National Environment al Management Act (NEMA) is ascertained amidst the existence of other laws of relevance and bye laws. Procedural steps taken in Marine Pollution management are highlighted preceding challenges and opportunities are summarized and conclusions are highlighted.